Chronic Kidney Disease and Urological Implications: The interplay between Chronic Kidney Disease and urological conditions - Shashi Kumar; N. Anil Kumar; C. Konda Reddy; Harsha Vardhana Varma Mudunuri (Orapuh, Inc., 2024)
Introduction People of all ages and cultures are affected by the diabetes crisis. The disease primarily affects the kidneys, heart, and nervous system and is categorised as type 1 or 2. Many urological problems can happen because diabetes and the urinary system work together in a complicated way, which is a cause for worry. Purpose The purpose of this research was to study Chronic Kidney Disease and their urological implications among the participants. Methods From November 2019 to November 2021, a retrospective analysis of 150 participants selected through the medical health records of Sri Venkateswara Institute of Medical Sciences, Tirupati, Andhra Pradesh, India, was carried out. We examined demographic and time-series trends, as well as the prevalence of chronic renal disease and urological diseases. We used descriptive statistics to understand the data to find trends and connections. Results The150 participants surveyed were 60% male and 40% female and the mean age of the participants was 55.2 years (SD: 8.7). The study indicated that the overall prevalence of CKD and urological problems among the participants was 30%. The prevalence of CKD among the participants was 20% (stage 1), 30% (stage 2), and 25% (stage 3). The prevalence of urological conditions was 15% (kidney stones), 20% (UTIs), and 10% (bladder dysfunction). Urological conditions tended to worsen with decline in kidney function. Conclusion The study underscores the significance of interdisciplinary cooperation in delivering effective patient care because of the complex relationship between urological disorders and CKD. Further investigation is necessary to enhance appro